The Paradox of Rechtsvinding in Criminal Law: The Tension Between the Principle of Formal Legality and the Expansion of Progressive Legal Interpretation in Indonesia - Reyhand Parlindungan; Fitri Rafianti; Bambang Fitrianto; Aries Kata Ginting; Daniel Naibaho (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The practice of judicial law-finding (rechtsvinding) in criminal law has consistently been confronted with a profound doctrinal tension between the demands of legal certainty and the pursuit of substantive justice. This study aims to examine the doctrinal boundaries and practical dynamics of judicial law-finding methods employed by judges in criminal cases in Indonesia following the enactment of the new National Criminal Code. The research adopts a normative juridical methodology utilizing statutory, conceptual, and jurisprudential approaches. The findings reveal that the principle of legality, embodied in the maxim nullum crimen, nulla poena sine praevia lege poenali, imposes strict limitations on judicial discretion by prohibiting the application of analogical reasoning (argumentum per analogiam) in criminal adjudication. Nevertheless, in responding to normative gaps arising from technological advancements and the increasing complexity of contemporary social and criminal phenomena, judges cannot remain passive as mere bouches de la loi (mouthpieces of the law). The paradigm of progressive law provides an avenue for judges to optimize legal interpretation, particularly through teleological (sociological) interpretation and extensive interpretation, without undermining the fundamental rights of defendants. Such interpretative methods enable courts to adapt legal norms to evolving social realities while remaining within the framework of criminal legality. This study concludes that a balance between formal legal certainty and substantive justice may be achieved when criminal law-finding is situated within the framework of protecting legally recognized social interests and guided by the principles of proportionality, objectivity, and rational legal reasoning. Accordingly, the future development of Indonesian criminal jurisprudence should not be directed toward abandoning the legality principle, but rather toward harmonizing legal certainty with the judicial responsibility to ensure that criminal law remains responsive to contemporary societal needs.